The Use of Hot Potatoes as Learning Media In Algebra Operations Material to Increase Activities and Learning Outcomes of Seventh Grade Students in SMP Al Hidayah Karangduren 2018/2019 Academic Year - Fitria Agustrianai (Universitas Islam Jember, 2019)
The purpose of this study was to describe how the process of using learning using Hot Potatoes Algebra Operations material for class VII students at Karangduren AL HIDAYAH Middle School. Then to find out the increase in the activity of students in algebraic surgery material by using Hot Potatoes media on class VII students at Karangduren AL HIDAYAH Middle School and to find out the increase in learning outcomes of algebraic surgery materials by using Hot Potatoes media in class VII students at AL HIDAYAH Middle School in 2018 / 2019. The type of this research is Classroom Action Research (CAR) using 2 cycles. Based on the results obtained from the percentage of student learning activities in learning cycle I was 82.81% with good categories and the second cycle was 89.06% with good categories. This shows an increase in student activity as much as 6.25%. The completeness of student learning outcomes in the prerequisite material obtained from the pre-cycle pretest was 66.66%. While the completeness of the results of the students in the first cycle reached 70.37% and experienced an increase in learning cycle II as much as 22.13% which obtained a percentage of 92.5% with a good category and has achieved classical completeness. However, in the second cycle, researchers conducted remedial so as to achieve 100% classical completeness. Keywords: Hot Potatoes, learning activities, learning outcomes